The Lithuanian Parliamentary Election and the Regional Press (2016) - Mažylė, Jolanta (Political Preferences, 2017)
Although an election campaign is a crucial part of political communication that encompasses much more than just development of media strategies or their implementation during elections, yet most solutions of modern election methods are based on the specifics of the mass media. The end recipient of information is misled if media outlets instead of disseminating information about a candidate and his intentions provide a distorted image of an election campaign. The image which is created when politicians seek to attract media attention by using their election methods (such as pseudo-events). Using literary and source analysis, the paper examines viewpoints of political scientists, sociologists, media and communication theory experts about the process of public information and its particularities during elections. Legal frame work regulating political advertising during elections in Lithuania is presented and the data of an empirical research – the content of the regional press during the 2016 elections to the Seimas (Parliament) of the Republic of Lithuania – is summarised focusing on the behaviour of the regional press. When analysing regional periodicals published during the election campaign, it was aimed to ascertain what roles the regional press chose – that of an observer or a watchdog, a provider of information or an analyst, an evaluator. Content analysis of regional press publications published during the election campaign and a sociological survey of media employees helps to determine what roles the media adopted. Key words: election campaign, press, voters, pseudo-events, partisanship, bias, agenda-setting, media